Non-market strategies and Indonesian SMEs: casualties of decentralisation?. Issue 2 (25th October 2018) - Sanusi, Abdullah; Connell, Julia
Abstract : Purpose: The purpose of this paper is to examine the non-market strategies adopted by government-contracted small and medium enterprises (SMEs) in order to address the challenges they faced in the business of procurement. Although SMEs are important contributors to employment and the national economy, they demonstrated different levels of effectiveness depending on the management strategies they adopted. Design/methodology/approach: Using case study methodology, data were gathered by conducting interviews with the owners/managers of Indonesian SMEs. Findings were analysed using the (ia) 3 framework developed to assist the understanding of non-market environments. Findings: Findings indicated that a key characteristic of the Indonesian non-market environment was the influence of the government and Indonesian society. This led to differing degrees of dissatisfaction among SME owners and managers who reported that they had to work within a number of constraints for business survival, while simultaneously learning how to "play the games" demanded by the business and regulatory environment. Research limitations/implications: Limitations relate to the number of empirical cases represented and the geographical area covered. Further research is recommended in order to provide the opportunity for research generalisation. Practical implications: These findings illustrate the need for transparency and integrity in the procurement process in relation to Indonesian SMEs. It is proposed that SMEs in similar sectors may benefit from forming strategic alliances/industry clusters to support future knowledge sharing and promote their collective voice. Originality/value: To date, studies on non-market strategies have largely focused on developed countries and large firms. Consequently, this paper goes some way towards bridging the gap in the non-market environment in developing countries concerning SMEs and potential strategies for adoption.